The Socio-Economic Struggles of the Main Character in The Wish Dragon (2021) by Chris Applehans - Ahmad Nurojab; Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2026)
This research aims to analyze: 1) the